Human resource development strategy in the context of operational management - Imam Wibowo (Journal of Economics and Business (JECOMBI), 2024)
This research aims to explore and analyze effective human resource (HR) development strategies in the context of operational management. Rapid technological developments and market dynamics require organizations to carry out their operations with efficiency and agility. Human resources as a key element in the entire operational process need to be managed and developed optimally. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of Human Resources (HR) development strategies in the context of operational management has a positive impact on organizational performance. Through training and development initiatives, companies are able to improve employee qualifications and increase operational productivity. A recruitment process that considers operational needs supports the placement of employees according to their skills, contributing to efficiency and effectiveness. The use of information technology, such as performance management systems and HR data analysis, provides a better information basis for making operational management decisions. In addition, building an organizational culture that encourages innovation and supports employee career development creates a motivating and competitive environment.